2023
DOI: 10.3390/ijms24032640
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of the Modified Lactoperoxidase System—In Vitro Studies on Human Gingival Fibroblasts

Abstract: One strategy in caries prevention is to inhibit the formation of cariogenic biofilms. Attempts are being made to develop oral hygiene products enriched with various antimicrobial agents. One of them is lactoperoxidase—an enzyme that can oxidise (pseudo)halide ions to reactive products with antimicrobial activity. Currently, commercially available products utilise thiocyanate as a substrate; however, several alternatives that are oxidised to products with greater antimicrobial potential have been found. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Finally, a necessary step will be to determine the lowest concentration of LPO system components that exhibit significant in vitro and in vivo antibiofilm effects while remaining nontoxic to host cells. In our previous studies on the toxicity of the described modifications in an LPO system against human gingival fibroblasts, we found that the LPO-I − system was characterised by the highest toxicity and the physiological system (LPO-SCN − ) by the lowest toxicity [29]. The results showed that modifying the LPO system enhances both its antibiofilm activity and its negative effects on host cells.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Finally, a necessary step will be to determine the lowest concentration of LPO system components that exhibit significant in vitro and in vivo antibiofilm effects while remaining nontoxic to host cells. In our previous studies on the toxicity of the described modifications in an LPO system against human gingival fibroblasts, we found that the LPO-I − system was characterised by the highest toxicity and the physiological system (LPO-SCN − ) by the lowest toxicity [29]. The results showed that modifying the LPO system enhances both its antibiofilm activity and its negative effects on host cells.…”
Section: Discussionmentioning
confidence: 86%
“…In the presented research, bovine milk LPO was used due to its high level of similarity (structural and functional) to the human LPO molecule [13]. A buffered solution of 50 nmol/L LPO was used throughout the study that reflected the physiological enzyme concentration found in saliva [29]. All LPO reactions were performed in phosphate buffered solution (PBS) at pH 7.4, which reflected the environmental conditions of the oral cavity of a healthy person between meals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations